UNIFICATION OF CONFLICT-OF-LAWS RULES IN THE FIELD OF INTELLECTUAL PROPERTY: A COMPARATIVE ANALYSIS OF INTERNATIONAL AND NATIONAL APPROACHES - Payzullaeva , Diyorakhon (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article provides a comparative analysis of international and national approaches to the unification of conflict-of-laws rules in the field of intellectual property. Based on the principles of lex loci protectionis and party autonomy, the study examines the European Union’s CLIP principles, the American Law Institute (ALI) principles, and WIPO multilateral conventions. Furthermore, it explores the current state of Uzbekistan’s legislation, intellectual property obligations within the framework of WTO accession, and develops scholarly recommendations for harmonizing the national legal system with international standards.